A cognitive‐behavioral program for parents of children with chronic musculoskeletal pain; A feasibility study. (23rd May 2017) - Wiertz, C.; Goossens, M.; Spek, E.M.; Verbunt, J.A.
Abstract: Background: The purpose of the study is to evaluate the feasibility of a newly developed parent program for parents of children with non‐specific chronic musculoskeletal pain. This program is part of the child's interdisciplinary outpatient pain rehabilitation treatment. The goal of the parent program is to change parent's thoughts/behaviour regarding pain with the ultimate intention to further improve their child's functioning. There were two main objectives in the study: First, to evaluate the feasibility of the parent program. Second, to evaluate changing in parental behavioral factors pre‐ and posttreatment. Methods: Participants were parents of adolescents, who underwent a interdisciplinary outpatient pain program for non‐specific chronic musculoskeletal pain. Parents participated in a parent program as part of their child's treatment. Adolescents reported their level of disability, pain intensity, fear of pain and pain catastrophizing by filling out questionnaires. Parents reported catastrophic thinking about their child's pain, fear of pain and disabilities of their child. In addition, they evaluated the parent program. Results: Sixty five parents (36 mothers and 29 fathers) of 44 adolescents filled in the baseline questionnaires. Result showed significant and clinically relevant improvements for both parents as well for adolescents. Parents were positive about the content of the parent program, they evaluated the program as supportive and informative. Conclusion: Adding a parent program to a interdisciplinary outpatient pain program for adolescent with chronic musculoskeletal pain, seems to be feasible in daily life of the parents and results in positive behavioural changes for both parents and adolescents. Significance: A parent program, designed to change cognition and behaviour of parents of children with chronic musculoskeletal pain is feasible.